Detoxification of Aflatoxin B1 by a Potential Probiotic Bacillus amyloliquefaciens WF2020 - Chen, Guojun; Fang, Qian’an; Liao, Zhenlin; Xu, Chunwei; Liang, Zhibo; Liu, Tong; Zhong, Qingping; Wang, Li; Fang, Xiang; Wang, Jie (Frontiers in Microbiology, 2022)
Microbial degradation is considered as an attractive method to eliminate the exposure of aflatoxin B1 (AFB1), the most toxic mycotoxin causing great economic losses and bringing serious threats to human and animal health, in food and feeds. In this study, Bacillus amyloliquefaciens WF2020, isolated from naturally fermented pickles, could effectively degrade AFB1 ranging from 1 to 8 µg/mL, and the optimum temperature and pH value was 37-45 °C and 8.0, respectively. Moreover, B. amyloliquefaciens WF2020 was considered to be a potential probiotic owing to the synthesis of active compounds, the absence of virulence genes, the susceptibility to various antibiotics, and the enhancement of Caenorhabditis elegans lifespan. The extracellular enzymes or proteins played a major role in the degradation of AFB1 mediated by B. amyloliquefaciens WF2020 into metabolites with low or no mutagenicity and toxicity to C. elegans. AFB1 degradation by the cell-free supernatant was stable up to 70 °C, with an optimal pH of 8.0, and the cell-free supernatant still could degrade AFB1 by 37.16% after boiled for 20 min. Furthermore, B. amyloliquefaciens WF2020 caused a slight defect in the fungal growth and completely inhibited the production of AFB1 when co-incubated with Aspergillus flavus. Additionally, B. amyloliquefaciens WF2020 suppressed the expression of ten aflatoxin pathway genes and two transcription factors (alfR and alfS), suggesting B. amyloliquefaciens WF2020 might inhibit the synthesis of AFB1 in A. flavus. These results indicate that B. amyloliquefaciens WF2020 and/or its extracellular enzymes or proteins have a promising potential to be applied in protecting food and feeds from the contamination of AFB1.